Developing Syllabus for IELTS Preparation Program: Focus on Grammar for Adult Learners (NOBEL: Journal of Literature and Language Teaching, 2021)
Since the IELTS test demands high English proficiency, it has become a challenge for Indonesian learners who are non-native English speakers. IELTS requires a thorough knowledge of English grammar to make the test takers able to gain high scores. The test-takers, who are mostly graduate students from various backgrounds, frequently join IELTS preparation classes. The previous research mainly focused on how teaching grammar is essential for students who want to take IELTS. Yet, the research about developing the syllabus for IELTS preparation classes has not been discussed much in Indonesia, making the information limited. Therefore, developing the syllabus for IELTS-based grammar is critically important since it assists the teacher in fulfilling students’ expectations and increases the student’s understanding of mastering English language skills. The current study aims at developing an IELTS-based syllabus for grammar to equip both students and teachers. The study adopted the developmental research proposed by Borg and Gall (2003). The syllabus was designed based on environment and need analysis obtained through interviews, placement tests, IELTS simulations, and questionnaires. The outcome is a three-part syllabus equipped with various learning activities to motivate and facilitate students to improve their grammar and ability to achieve higher IELTS scores.